Glutaraldehyde modification of lipases immobilized on octyl agarose beads: Roles of the support enzyme loading and chemical amination of the enzyme on the final enzyme features - Abellanas-Pérez, Pedro; Carballares, Diego; Fernández-Lafuente, Roberto; Rocha-Martín, Javier (Elsevier BV, 2023)
Lipase B from Candida antarctica (CALB) and lipase from Thermomyces lanuginosus (TLL) have been immobilized on octyl agarose at low loading and at a loading exceeding the maximum support capacity. Then, the enzymes have been treated with glutaraldehyde and inactivated at pH 7.0 in Tris-HCl, sodium phosphate and HEPES, giving different stabilities. Stabilization (depending on the buffer) of the highly loaded biocatalysts was found, very likely as a consequence of the detected intermolecular crosslinkings. This did not occur for the lowly loaded biocatalysts. Next, the enzymes were chemically aminated and then treated with glutaraldehyde. In the case of TLL, the intramolecular crosslinkings (visible by the apparent reduction of the protein size) increased enzyme stability of the lowly loaded biocatalysts, an effect that was further increased for the highly loaded biocatalysts due to intermolecular crosslinkings. Using CALB, the intramolecular crosslinkings were less intense, and the stabilization was lower, even though the intermolecular crosslinkings were quite intense for the highly loaded biocatalyst. The stabilization detected depended on the inactivation buffer. The interactions between enzyme loading and inactivating buffer on the effects of the chemical modifications suggest that the modification and inactivation studies must be performed under the target biocatalysts and conditions. © 2023 The Authors DC thank to Ministerio de Ciencia e Innovaci´on-Spanish Government for a FPI. This research was funded by Ministerio de Ciencia e Innovaci´on and Agencia Estatal de Investigaci´on (Spanish Government) (PID2022-136535OB-I00 and TED2021-131462B-I00). We gratefully recognized Prof. ´Angel Berenguer-Murcia for his suggestions and help during the writing of this paper. Supplementary data to this article can be found online at https://doi.org/10.1016/j.ijbiomac.2023.125853 Peer reviewed